The Gender Health Gap in Ghana: Exploring the Role of Financial Inclusion - Iddrisu, Abdul Ganiyu; Mohammed, Jabir Ibrahim; Darius, Ibzan; Bakth, Nazmunnesa (Review of Economic Analysis, 2025)
This paper investigates the impact of financial inclusion on health and the gender-health differences in Ghana using microdata from the sixth wave of the Ghana Living Standards Survey (GLSS) and instrumental variable techniques. The findings reveal significant gender health differences, with women reporting lower health than men. Importantly, the study suggests that financial inclusion could be a powerful tool in reducing the gender-health gap, as individuals with higher financial inclusion levels report better health. Furthermore, there is no significant health difference across genders for people with a higher level of financial inclusion. These findings have novel and important policy implications, highlighting the potential of financial inclusion in addressing the gender-health gap in Ghana.